Analisis Strategi Pemerintah Desa Dalam Pemeliharaan Infrastruktur Jalan Di Desa Purwodadi Kabupaten Tanjung Jabung Barat - Zunnun Alfaid Nurudin Rasyidy; Dahmiri; Ovie Yanti (Jurnal Ekonomi dan Bisnis Digital, 2025)
Road infrastructure problems usually occur in rural areas. Damage to road shoulders, road facilities, and potholes that grow larger over time due to increasing mobility every year is one of the issues that needs to be addressed by local governments, especially in rural areas. The purpose of this study is to identify and analyze the strategies, obstacles, and solutions implemented by the village government in maintaining road infrastructure in Purwodadi Village, Tebing Tinggi District, Tanjung Jabung Barat Regency. This study uses a qualitative research design with a descriptive analysis approach. The data used are from primary and secondary sources, with informants selected using purposive sampling. There were 11 informants in this study, consisting of the village head, village secretary, village officials, and hamlet heads. The results of the study show several strategies used by the village government in road infrastructure maintenance, namely coordination, consistency, synchronization, prioritization and priority scale, community participation, and problem solving. The obstacles faced were the lack of responsiveness from the regional government, limited village funds and vast territory, lack of human resources, and road locations with peat soil. The solutions used are to always be consistent, use PADesa, continue education, and interact with experts and the village community.